The opportunity model of organizational commitment: Evidence from white-collar employees in Turkey. Issue 2 (2nd May 2017) - Cicekli, Elif; Kabasakal, Hayat
Abstract : Purpose: The purpose of this paper is to determine the relationships between promotion, development, and recognition opportunities at work and organizational commitment, and whether these relationships are moderated by the job opportunities employees have in other organizations. Design/methodology/approach: An opportunity model of organizational commitment is developed based on social exchange theory and several streams of opportunity research. Factor analyses and hierarchical multiple regression analyses are carried out to test the hypotheses using data from 550 white-collar employees. Findings: The results of the analyses show that opportunities for development and recognition are predictors of organizational commitment, that job opportunities employees have in other organizations negatively moderate the relationship between recognition opportunity at work and organizational commitment, and that promotion opportunity does not predict organizational commitment. Research limitations/implications: Future researchers could study the issue in the context of other cultures using data from multiple sources. Practical implications: Employers who seek to increase their employees' organizational commitment are advised to divert their energies from struggling to create promotion opportunities for their employees to creating opportunities for development and recognition. Originality/value: The study explores the under-researched concept of opportunity at work and connects several streams of opportunity research by drawing on social exchange theory as a theoretical framework. The model is the first to address the effects of opportunity and alternative opportunities on organizational commitment.